Design and Characterization of a Non-Linear Variable Inerter in Vehicle Suspension System - Y., Goh K.; F., Soong M.; R., Ramli; A.A., Saifizul; S.Y., Khoo (International Journal of Integrated Engineering, 2023)
Inerter is a two-terminal component in suspension system such that the force at the two terminals is directly proportional to the relative acceleration of these two points. Studies have shown that the inerter can provide satisfactory vibration isolation for a number of suspension applications, including train suspension, building suspension and vehicle suspension. In the context of vehicle suspension, the existing passive inerter has been shown to provide benefits to vehicle dynamics performance measures, such as ride comfort and road holding ability. However, a basic passive inerter has fixed characteristic, and hence its potential is limited. This study overcome this limitation by incorporating variable inertia in inerter flywheel, however its non-linear characteristic needs to be determined. The method of achieving variable inertia in inerter flywheel is through introduction of movable masses or sliders attached with springs into inerter flywheel. The change of moment of inertia is caused by position change of sliders due to centrifugal force when the flywheel is rotating. Results showed that the proposed variable inerter exhibits a non-linear force-acceleration relationship with respect to its operating rotational speed. A vehicle suspension system equipped with a variable inerter is also able to further reduce vertical vehicle body acceleration and vehicle’s dynamic tire load when compared with vehicle suspension system without inerter and equipped with a passive inerter, which indirectly relates to a better vehicle ride and handling performance improvements. Hence, it can be proved that the proposed variable inerter is better than a passive inerter and is able to provide better ride comfort and road holding ability to a vehicle.